Interface matters: Design of an efficient CaCu3Ti4O12-rGO photocatalyst - Praxedes, F. M. [UNESP] (2022)
Different strategies have been investigated to enhance optical properties of semiconductor oxides such as CaCu3Ti4O12, e.g., reduced graphene oxide. This research focuses on photoluminescent and photocatalytic properties of CaCu3Ti4O12-rGO composites. Micrometric CCTO and rGO particles were mixed to obtain composites. (Micro)structure, photoluminescence, and photocatalytic properties were evaluated. CCTO-rGO composites displayed broad PL emission over the visible spectrum, useful for triggering photocatalytic applications (≈ 380–750 nm). A shift in PL towards the violet region compared to pure CCTO along with an associated orange emission decrease may be ascribed to rGO activity as an electron donor/acceptor. Photocatalytic tests under UV light (325 nm) showed that 20%rGO (≈ 25.88%) significantly improved rhodamine B removal/adsorption compared to pure CCTO (≈ 9.64%). Results from this study show that CCTO-rGO composites may be a promising choice for future UV–visible light-driven photocatalytic devices with high adsorption/lower response time promoting sustainability in water purification methods and associated applications.